2014
DOI: 10.1088/0953-8984/26/31/315012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen retention and diffusion in tungsten beryllide

Abstract: Beryllide compounds are often used in various domains because they are more resilient to oxidation than pure beryllium and at the same time they keep some of the properties of this metal. Nevertheless, the data about their properties during atomic hydrogen exposure are very scarce: numerous experiments have been conducted in the past few years on solid hydride deposition under beryllium-seeded plasma action or on energetic hydrogen implantation into metallic beryllium; many others have been devoted to hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Previous theoretical studies by density functional theory (DFT) calculations reported defect formation energies for various types of defects in metallic Be and beryllides. , The calculated vacancy formation energies at Be i ( i = 1,2, 3) sites in Be 12 Ti and Be 12 V were in the range 1.43–1.64 eV, which were significantly higher than that in metallic Be (1.09 eV). Such increases of Be vacancy formation energy have also been reported for Be 12 W . D. V. Bachrin et al predicted that Be 12 Ti has a lower hydrogen isotope binding energy compared with that of Be, by at least 0.4 eV .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous theoretical studies by density functional theory (DFT) calculations reported defect formation energies for various types of defects in metallic Be and beryllides. , The calculated vacancy formation energies at Be i ( i = 1,2, 3) sites in Be 12 Ti and Be 12 V were in the range 1.43–1.64 eV, which were significantly higher than that in metallic Be (1.09 eV). Such increases of Be vacancy formation energy have also been reported for Be 12 W . D. V. Bachrin et al predicted that Be 12 Ti has a lower hydrogen isotope binding energy compared with that of Be, by at least 0.4 eV .…”
Section: Introductionsupporting
confidence: 57%
“…14,15 The calculated vacancy formation energies at Bei (i = 1,2, 3) sites in Be 12 Ti and Be 12 V were in the range 1.43-1.64 eV, which were significantly higher than that in metallic Be (1.09 eV). Such increases of Be vacancy formation energy have also been reported for Be 12 W. 16 D. V. Bachrin et al predicted that Be 12 Ti has a lower hydrogen isotope binding energy compared with that of Be, by at least 0.4 eV. 17 Burr et al reported that the Be-Fe(-Al) intermetallics have much lower oxygen affinity than metallic Be by calculating solution energies of oxygen.…”
Section: Introductionmentioning
confidence: 65%
“…This lower diffusivity for H atoms in Be 22 W can impede the movement of H atoms. 1.03 Be 12 W W 3.00 [14] Be 1.14-1.48 [14] Pure W W 3.26, 3.33, [10] 3.25 [14] Pure Be Be 1.09, 0.95, [9] 1.11 [28]…”
Section: Methodsmentioning
confidence: 99%
“…[8] However, the corresponding research on H behavior in Be-W materials is still lacking. [14] From a more fundamental point of view, it is interesting to analyze the influence of the secondary element (W) with rich electrons on the solubility and diffusion of H in the poor-electron element (Be). Furthermore, the physicochemical properties of the mixed materials and alloys are essential input data needed for the modeling of erosion, transport, and deposition in large-scale codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation